Review and modeling of vegetation propagation model for wireless sensor networks using OMNeT++ - Munirah L., Kamarudin; R. Badlishah, Ahmad, Dr.; Ong, Bi Lynn; Fareq, Malek, Dr.; A., Zakaria; Mohd Arif, M. A. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/